Notch Signaling Components: Diverging Prognostic Indicators in Lung Adenocarcinoma. Issue 20 (May 2016) - Liu, Zhi-Yan; Wu, Tao; Li, Qing; Wang, Min-Cong; Jing, Li; Ruan, Zhi-Ping; Yao, Yu; Nan, Ke-Jun; Guo, Hui
Abstract : Abstract: Non-small-cell lung cancer (NSCLC) is a lethal and aggressive malignancy. Currently, the identities of prognostic and predictive makers of NSCLC have not been fully established. Dysregulated Notch signaling has been implicated in many human malignancies, including NSCLC. However, the prognostic value of measuring Notch signaling and the utility of developing Notch-targeted therapies in NSCLC remain inconclusive. The present study investigated the association of individual Notch receptor and ligand levels with lung adenocarcinoma (ADC) and squamous cell carcinoma (SCC) prognosis using the Kaplan-Meier plotte database. This online database encompasses 2437 lung cancer samples. Hazard ratios with 95% confidence intervals were calculated. The results showed that higher Notch1, Notch2, JAG1, and DLL1 mRNA expression predicted better overall survival (OS) in lung ADC, but showed no significance in SCC patients. Elevated Notch3, JAG2, and DLL3 mRNA expression was associated with poor OS of ADC patients, but not in SCC patients. There was no association between Notch4 and OS in either lung ADC or SCC patients. In conclusion, the set of Notch1, Notch2, JAG1, DLL1 and that of Notch3, JAG2, DLL3 played opposing prognostic roles in lung ADC patients. Neither set of Notch receptors and ligands was indicative of lung SCC prognosis. Notch signaling could serve as promising marker to predict outcomes in lung ADC patients. The distinct features of lung cancer subtypes and Notch components should be considered when developing future Notch-targeted therapies. Abstract : Supplemental Digital Content is available in the text